2009
DOI: 10.1007/s11747-009-0165-x
|View full text |Cite
|
Sign up to set email alerts
|

Service firms and customer loyalty programs: a regulatory fit perspective of reward preferences in a health club setting

Abstract: In this paper, we examine the impact of various configurations of regulatory fit on the attitudes, exercise intentions and actual behavior of members of a health club loyalty program. Regulatory fit is conceptualized as both the match between types of program rewards and how they are communicated, as well as the congruence between reward types and regulatory focus as a stable, individual disposition. In two experimental designs, non-point reward programs offering a short-term cash bonus were used. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 45 publications
(83 reference statements)
3
54
1
2
Order By: Relevance
“…Members respond more favorably to delayed rewards that have high goal congruity and fit with their personal values (e.g., health club gift certificate for members who favor a healthy lifestyle). However, the importance of the fit is attenuated by the communication of the rewards: The strongest impact on perceptions and behavior occurs when prevention-focused members obtain a preventionframed reward and promotion-focused members, a promotion-framed reward (Daryanto et al, 2010).…”
Section: Frequency Reward Programsmentioning
confidence: 99%
“…Members respond more favorably to delayed rewards that have high goal congruity and fit with their personal values (e.g., health club gift certificate for members who favor a healthy lifestyle). However, the importance of the fit is attenuated by the communication of the rewards: The strongest impact on perceptions and behavior occurs when prevention-focused members obtain a preventionframed reward and promotion-focused members, a promotion-framed reward (Daryanto et al, 2010).…”
Section: Frequency Reward Programsmentioning
confidence: 99%
“…Due to heightened motivation and engagement, both the attraction to (in case of fit) and repulsion from (in case of misfit) a target is magnified (Hong & Lee, 2008); indeed, "when people experience strong engagement with something, they are involved, occupied, interested and attentive to it" (Higgins, 2006, p. 451). For example, Daryanto, de Ruyter, Wetzels, and Patterson (2010) showed that regulatory fit improves people's exercise behavior in terms of intensity and intentions by increasing their engagement with the focal activity. Following this rationale, it is hypothesized that promotion-(prevention) focused individuals would feel right about their goal pursuit activities and experience heightened engagement when exploring a hedonic (utilitarian) website.…”
Section: Regulatory Fit and Engagementmentioning
confidence: 99%
“…Promotion or prevention characteristics of products have been so far evaluated in experimental pre-tests based on definitions or single question evaluations (Ku, Kuo andKuo 2012, Keeling et al 2013) and confirmed later in experimental designs. There is significant experimental evidence that a match between chronic/primed goal orientation and an inferred (but not reliably measured) product orientation creates the effects of regulatory fit (RF) (Higgins 2006), such as, 'feeling right' about and further engagement with goal pursuit, positive goal evaluations, affective reactions, enhanced intentions and behavior (Higgins et al 2003, Daryanto et al 2010). Zhou and Pham (2004) find that levels of investment in financial products and services (e.g., trading account vs. mutual fund) offering either nurturance or security benefits differ as a function of match/mismatch of a service with an appropriate gain or loss framed message.…”
Section: Promotion or Prevention Function Of Different Productsmentioning
confidence: 99%
“…(1998) and Daryanto et al (2010) (1-not at all, 9-very much) (α = .90), and 'How easy would it be for you to use this tool?' (1-very difficult, 9-very easy).…”
Section: H1b Match (Fit) Of Individual Orientation With Tool Predictmentioning
confidence: 99%